Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1038/9195
|View full text |Cite
|
Sign up to set email alerts
|

The tetrodotoxin-resistant sodium channel SNS has a specialized function in pain pathways

Abstract: Many damage-sensing neurons express tetrodotoxin (TTX)-resistant voltage-gated sodium channels. Here we examined the role of the sensory-neuron-specific (SNS) TTX-resistant sodium channel alpha subunit in nociception and pain by constructing sns-null mutant mice. These mice expressed only TTX-sensitive sodium currents on step depolarizations from normal resting potentials, showing that all slow TTX-resistant currents are encoded by the sns gene. Null mutants were viable, fertile and apparently normal, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
533
7
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 727 publications
(583 citation statements)
references
References 38 publications
31
533
7
5
Order By: Relevance
“…Consistent with this notion, SCN5A is primarily expressed in cardiac tissue, while SCN10A and SCN11A transcripts are found in peripheral nociceptive sensory neurons (Akopian et al 1999;Dib-Hajj et al 1999a;Amaya et al 2000). SCN5A expression also occurs in central nervous system regions associated with the limbic system (Donahue et al 2000;Hartmann et al 1999).…”
Section: Scna Gene Expression In Teleosts and Mammalsmentioning
confidence: 52%
“…Consistent with this notion, SCN5A is primarily expressed in cardiac tissue, while SCN10A and SCN11A transcripts are found in peripheral nociceptive sensory neurons (Akopian et al 1999;Dib-Hajj et al 1999a;Amaya et al 2000). SCN5A expression also occurs in central nervous system regions associated with the limbic system (Donahue et al 2000;Hartmann et al 1999).…”
Section: Scna Gene Expression In Teleosts and Mammalsmentioning
confidence: 52%
“…Tetrodotoxin-resistant voltage-dependent sodium channels Nav1.8 (SNS) and Nav1.9 (NaN or SNS2) are selectively expressed in small/medium-sized nociceptive neurons and contribute to the production of an action potential in these neurons. In addition, functional studies reveal that Nav1.8 and Nav1.9 have a specialized role in mediating pain [1,2,[15][16][17]. Thus, the level of gene expression and/or distribution of these channels may be altered in aging neurons that have lowered sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The depolarization of the membrane potential of 8‐month‐old IB4+ neurons is important, as it nears the activation potentials of the TTX‐R Nav1.8 isoform (~−40 mV), which was shown to be the main Na + channel isoform underlying the majority of the current during AP upstroke and key to enabling repetitive firing in mouse DRG neurons (Akopian et al., 1999; Renganathan et al., 2001). Indeed, we found that the IB4+ neurons from 8‐month‐old animals receive the highest contribution from the TTX‐R window current at rest (Figure 6b).…”
Section: Discussionmentioning
confidence: 99%